2011
DOI: 10.5194/acp-11-9519-2011
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake by biomass burning aerosol at sub- and supersaturated conditions: closure studies and implications for the role of organics

Abstract: Abstract. We investigate the CCN activity of freshly emitted biomass burning particles and their hygroscopic growth at a relative humidity (RH) of 85 %. The particles were produced in the Mainz combustion laboratory by controlled burning of various wood types. The water uptake at sub-and supersaturations is parameterized by the hygroscopicity parameter, κ (c.f. Petters and Kreidenweis, 2007). For the wood burns, κ is low, generally around 0.06. The main emphasis of this study is a comparison of κ derived from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 47 publications
(63 reference statements)
4
92
0
Order By: Relevance
“…The previous work of Dusek et al (2011) has investigated conceptually the importance of fractal morphology in CCN analysis. We present experimental data for both the hygroscopicity and morphology of the particle and apply it to κ-Köhler analysis.…”
Section: Applying a True Volume Equivalent Diameter To The Ccn Analysmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous work of Dusek et al (2011) has investigated conceptually the importance of fractal morphology in CCN analysis. We present experimental data for both the hygroscopicity and morphology of the particle and apply it to κ-Köhler analysis.…”
Section: Applying a True Volume Equivalent Diameter To The Ccn Analysmentioning
confidence: 99%
“…Both this work and Martin et al observed the effect that aging has on particle morphology and how that impacts κ, but here we are able to quantify the changes in morphology through empirical constructs such as fractal-like dimension. It remains that the magnitude of particle nonsphericity and its effect on hygroscopicity has only been theoretically manipulated and not experimentally measured, especially as a function of particle aging (Dusek et al, 2011). Here we provide simultaneous morphological and hygroscopicity measurements of fresh and aged biomass aerosol.…”
Section: Biomass Burning Cloud Condensation Nucleimentioning
confidence: 99%
“…Water uptake properties of biomass burning particles, including those emitted from peatlands, have been explored in a laboratory through measurements of hygroscopic growth and CCN activity (Chand et al, 2005;Dusek et al, 2005Dusek et al, , 2011Day et al, 2006;Petters et al, 2009;Carrico et al, 2010). In general, freshly emitted biomass burning particles have been found to be hygroscopic.…”
Section: Introductionmentioning
confidence: 99%
“…The annual globally burned land area is in the range of 3 to 3.5 million square kilometers, resulting in emissions amounting to 2.5 × 10 9 kg carbon per year (van der Werf et al, 2006;Schultz et al, 2008). Particles in biomass burning smoke enriched with hygroscopic organic and inorganic constituents are suggested to act as efficient cloud condensation nuclei (Novakov and Corrigan, 1996;Petters et al, 2009;Rissler et al, 2010;Dusek et al, 2011;Frosch et al, 2011). In the Amazon basin, for example, the CCN concentration in the dry season is 1 order of magnitude higher than in the wet season due to biomass burning (Roberts et al, 2001;Carrico et al, 2008;Hening et al, 2010).…”
Section: Introductionmentioning
confidence: 99%